EVALUASI STATUS KESUBURAN N P K TANAH SAWAH TADAH HUJAN DI KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Fitra Syawal Harahap (UNIVERSITAS LABUHANBATU, 2018)
Rainfed rice fields are paddy fields whose water sources depend on rainfall without permanent irrigation structures. This study aimed to identify fertility variables that are obstacles in Beringin Subdistrict by evaluating soil fertility status and reviewing management alternatives that are in accordance with the soil fertility status found in rainfed lowland rice fields in several villages in Beringin Subdistrict, Deli Serdang District.This research was a phenomenological qualitative descriptive study with land survey and supported by qualitative laboratory analysis. The taking of soil samples was carried out in the survey area sequentially based on the location of the estimated nature of the soil with the purposive random sampling method. The taking of soil samples was taken in the upper layer at the top soil depth of 0-20 cm, and the coordinates of the point were recorded using GPS.The fertility status of paddy fields in BeringinSubdistrict was classified as high, medium, and low soil fertility status. High soil fertility in P-total soil parameters in all villages, for medium land in K2O parameters in all villages, while for low land status in N-total land parameters in all villages. Prompts for giving urea fertilizer without organic matter as much as 250 kg ha-1, with 5 tons of straw ha-1 adding urea fertilizer as much as 230 kg ha-1 and using 2 tons of manure ha-1 giving urea fertilizer as much as 225 kg ha-1.P fertilization in medium status paddy fields is 75 kg SP-36 ha-1, and high P fertility status is 50 kg ha-1SP-36. K fertilizer application for high soil fertility status is 50 kg ha-1. Prompts for organic fertilizer using compost of rice straw equal to 5 tons ha-1 and or manure 2 tons ha-1. Keywords: Status of N,P,K, Rainfed Rice Field, Beringin District